Do tax loss restrictions distort venture capital funding of start-ups? - Anna Theresa Bührle (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Anti-tax loss trafficking rules disallow the use of loss carryforwards after a change in ownership or activity (such as significant changes in turnover, employment, or the product portfolio). This restriction could threaten accumulated loss carryforwards of start-ups. Accounting for the increased risk and reduced return on their investment, VC investors could reduce their funding. I analyze whether the venture capital (VC) funding of start-ups in Europe is affected by these regulations. I base my empirical analysis on several case studies and a panel analysis covering VC- funded companies in the EU28 Member States from 1999 to 2014. My findings suggest that strict anti-tax loss trafficking rules indeed impair VC funding. Especially more mature companies and companies in high-tech industries are affected.
Keywords: M13; G24; H25; 330; Venture capital; taxes; loss carryforward; start-ups; anti-tax loss trafficking